Enhancement of multicast network security - Ali, Sellami; Mahmoud, Omer; Wahid, Zaharah; Chowdhury, Md. Sazzad Hossien (Kaerntner Botanikzentrum, Klagenfurt, Austria, 2013)
The need for communications networks is quite evident in the world today, multicasting has becomes a major way of transferring digital data to huge number of audience. The advantages of multicast in multi-party communications, such as saving bandwidth, simplicity and efficiency, are very essential for new services that combine voice, video and text over Internet. It has many applications in online multimedia and sensor networks and so on. The multicast networks distribute sensitive or private information, therefore they must be provided via secure communication channels. In this paper, the security of multicast network has been reviewed. A method has been presented to improve the security of multicast network (SMN) using quantum key distribution (QKD) network. This technique protected multicast network against internal and external impersonation. The QKD has been added to multicast network architecture to generate the secure keys. The keys are in the authentication and encryption processes. The proposed scheme aimed to provide a secure end to end communication for multicast network.